Different characteristics of independent and compound extreme heat and ozone pollution events in the Greater Bay Area of China - Ziwei Huang; Ming Luo; Meng Gao; Guicai Ning; Erjia Ge; Ting On Chan; Sijia Wu; Hui Zhang; Yu Tang (International Journal of Applied Earth Observations and Geoinformation, 2023)
Under global warming and rapid urbanization, heat extremes, ozone pollution, and their co-occurrences are emerging and posing severe risks to human health. However, possibly different characteristics of independent heat days (IHD), independent ozone pollution (IOP) and compound heat-ozone pollution (CHOP) events are unclear. In this study, we present an investigation of the spatial distribution and mechanisms associated with IHD, IOP and CHOP events during May–October in 2014–2022 by taking the Guangdong-Hong Kong-Macao Greater Bay Area (GBA) of China as an example. The results show that central GBA faces higher compound risk than northwestern and southeastern regions. IHD events are primarily driven by extremely high temperatures and accompanied by anomalous anticyclone and high pressure at both lower and upper troposphere levels, under the joint effects of the South Asian high and western North Pacific subtropical high. IOP events are predominantly accompanied by decreased cloud cover, air humidity and enhanced downward solar radiation. CHOP events are influenced by increases in both temperature and downward solar radiation. The circulation patterns of CHOP events are somewhat similar to IOP but with much stronger magnitude and faster developing process, and both are likely related to tropical cyclone activities. Our findings can strengthen the early forecasting of these extreme events and mitigate their negative impacts.